Learning a trauma-sensitive sport model: training workshop experiences - Shaikh, M.; Culver, D. M.; Forneris, T. (International Sport Coaching Journal, 2026)
The purpose of this study was to explore leaders` development of trauma-sensitive approaches in their sport coaching practices through exploring the learning experiences of leaders of a national community youth-serving organisation who participated in an initial training workshop. The value-creation framework was used to explore learning experiences based on the interactions and values leaders discussed. Two training workshops were held with two different cohorts of leaders. The researcher observed these workshops, and the leaders were interviewed about their preferences for training and development, and their experiences of learning in the workshops. The interview data were analysed collectively using a deductive-inductive thematic analysis. Data were also collected on leaders` satisfaction with training, knowledge perceptions, content knowledge, and attitudes toward trauma-sensitive practice. These data were analysed using descriptive statistics and Wilcoxon signed-ranks tests. Collectively, the results showed that the leaders (a) improved their relevant knowledge from pre- to postparticipation; (b) valued having a variety of learning opportunities; (c) wanted to learn how to support their youth`s needs better within and beyond sport; and (d) intended to promote more responsive, trauma-sensitive programme practices. Implications were discussed for the improvement of training opportunities to meet learners` needs.